IoT : development of a home automation system 3 - Tan, Yong Rui (Nanyang Technological University, 2019)
This project proposes a platform for Home Automation IoT (Internet of Things) devices with different hardware and IoT protocols. Portable devices such as mobile phone provides user interface to interact with these IoT devices. A skill for virtual assistant, Alexa is also developed to control and retrieve readings from the IoT devices. This project is a full implementation of Home Automation from the physical hardware to the back-end servers and front-end user interface. The overall system will consist of a total of 5 IoT devices, environmental sensors, soil moisture sensor, an LED lamp, a sound buzzer and a third party IoT sensor that is integrated into this platform. This project aims at controlling and monitoring home IoT devices with a single platform which is accessible anytime with internet connection. Furthermore, it also aims to explore different IoT protocols which is optimal for the specific use cases.